Dr. Strangelove or: How I Learned to Stop Worrying and Love the Bomb - Kubrick, Stanley (USA, 1964)
Fearful that the Russians are fluoridating America's drinking water, General Jack D. Ripper unleashes a B-52 H-Bomb attack on the Soviets, and a frantic President and Joint Chiefs of Staff must somehow find a way to stop it.
Keywords: Fiction films